A New Vision of Teaching Clinical Pharmacology and Therapeutics for Undergraduate Medical Students - Alsanosi, Safaa M (Advances in medical education and practice, 2022)
For many years, clinical pharmacology (CP) has been taught at schools of medicine via traditional methods including classic lectures and experimental sessions. The explosion of scientific knowledge and the availability of many treatment options have necessitated the development of new strategies for pharmacology teaching and learning. Applying information learnt in real-life situations has become more important than finding information that is readily available in many places. The newly implemented reformed curriculum at Umm Al Qura University - Faculty of Medicine (UQUMED) is a student-centred, competency-based curriculum with enhanced integration across the disciplines. Teachers and students have a great responsibility in updating the curriculum. The "Use of Medicine" (UofM) vertical module is part of this reformed curriculum that focuses on key principles, a core list of medications, the vertical and horizontal integration of subjects, the knowledge application to real case situations, enhanced critical thinking and self-learning. It emphasizes rational prescribing, safe medical practice and excellence in teaching CP and therapeutics. The adoption of newer and innovative teaching and assessment methods and the training of faculty/staff can help to refresh CP education. One challenge in CP education is that teachers are shifting from acting as information providers to acting as facilitators so that students become life-long learners. The assessment of our reformed curriculum uses several valid reliable tools to evaluate the achieved skills and competencies. This manuscript describes the transformational changes in CP education at UQU up to the development and implementation of the UofM vertical module as part of the reformed UQUMED curriculum. Continuous updates in CP education are critical for rational, safe, and affordable medication prescribing for better patient care.